A Comparative Study of Higher Education Governance in Greater China - Tao, Claire Y.H. (International Dialogues on Education Journal, 2020)
During 1980, many Western countries launched public administration reforms. These reform waves also blew over to many Asian countries. With the advent of globalization and the rise of knowledgebased society, education and innovation are regarded as the driving forces behind social and economic growth and development. To enhance the national capacity, education reforms have also become common agendas among nation states since the 1980s. This paper aims at critically reviewing and comparing major policies and strategies of the higher education reform adopted by the respective government in Greater China, including mainland China, Hong Kong, Macau, and Taiwan and Singapore. The key research questions are why these countries attempted to reform their higher education and if these countries achieve the desired results and comply with good governance. In this paper, four areas, "Rule of Law," "Transparency," "Effectiveness," and "Accountability" are evaluated to examine how these selected cases’ governance in higher education have been implemented in the past 30 years.